The variation in isometric tension with sarcomere length in vertebrate muscle fibres - Gordon, A. M. (1966)
1. The variation of isometric tetanus tension with sarcomere length in single fibres from frog striated muscle has been re-investigated with special precautions to ensure uniformity of sarcomere length within the part of the fibre being studied. 2. In most respects the results of Ramsey & Street (1940) were confirmed, but (a) the peak of the curve was found to consist of a plateau between sarcomere lengths of 2·05 and 2·2 μ, (b) the decline of tension above this plateau is steeper than found by Ramsey & Street, and (c) the decline of tension below the plateau becomes suddenly steeper at a sarcomere length of about 1·67 μ. 3. Many features of this length—tension relation are simply explained on the sliding-filament theory. 4. It is concluded that, in the plateau and at greater lengths, the tension on each thin filament is made up of equal contributions from each bridge which it overlaps on adjacent thick filaments. 5. Internal resistance to shortening is negligible in this range but becomes progressively more important with shortening below the plateau.